1993
DOI: 10.1111/j.1095-8649.1993.tb01182.x
|View full text |Cite
|
Sign up to set email alerts
|

Variability in the distribution and abundance of stream salmonids, and the associated use of habitat models

Abstract: The effective management of salmonid fisheries requires that the factors influencing variation in the abundance of stream populations are understood. The use of habitat models to explain the spatial component of population variance offers potential for management, but has not previously been set in the context of long term variation in population abundance because of the lack of suitable data sets. This paper examines contributions of spatial and temporal factors lo fish density variance using a 10‐year data s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

1995
1995
1998
1998

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 11 publications
0
19
0
Order By: Relevance
“…The methods outlined here refer to two différent exercises : a habitat modelling and catchment scale variance partitioning on the Conwy (MILNER et al, 1993) and a more récent development using improved techniques in a national scale habitat modelling project (WYATT etal., 1995).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The methods outlined here refer to two différent exercises : a habitat modelling and catchment scale variance partitioning on the Conwy (MILNER et al, 1993) and a more récent development using improved techniques in a national scale habitat modelling project (WYATT etal., 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Model parameters have been reported elsewhere (MILNER et al, 1993). Performance as measured by the percentage of population density (independent data set) variance (R^, adj %) explained by the models were 72.4, 66.2, 48.3 and 26.2 % for trout 0*, trout >0"^ and salmon >0* respectively.…”
Section: Habitat Survey and Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier work (MILNER et al, 1993) demonstrated the need to examine the contributions made by the différent potential sources of variation to the overall variablity of the data-set. Techniques were devised to effectively 'partition' the variance in a data-set to allow the true variation due to spatial factors to be derived (see, for example, MILNER et al, 1993).…”
Section: Nb : % Fit Represents the Percentage Of The Spatial Componmentioning
confidence: 99%
“…Techniques were devised to effectively 'partition' the variance in a data-set to allow the true variation due to spatial factors to be derived (see, for example, MILNER et al, 1993). In gênerai terms, the spatial variance component is all that can be hoped to be accounted for by habitat models.…”
Section: Nb : % Fit Represents the Percentage Of The Spatial Componmentioning
confidence: 99%